The hydraulic mechanism in the hind wing veins of Cybister japonicus Sharp (order: Coleoptera) - Sun, Jiyu; Wu, Wei; Ling, Mingze; Bhushan, Bharat; Tong, Jin (Beilstein Journal of Nanotechnology, 2016)
The diving beetles (Dytiscidae, Coleoptera) are families of water beetles. When they see light, they fly to the light source directly from the water. Their hind wings are thin and fragile under the protection of their elytra (forewings). When the beetle is at rest the hind wings are folded over the abdomen of the beetle and when in flight they unfold to provide the necessary aerodynamic forces. In this paper, the unfolding process of the hind wing of Cybister japonicus Sharp (order: Coleoptera) was investigated. The motion characteristics of the blood in the veins of the structure system show that the veins have microfluidic control over the hydraulic mechanism of the unfolding process. A model is established, and the hind wing extending process is simulated. The blood flow and pressure changes are discussed. The driving mechanism for hydraulic control of the folding and unfolding actions of beetle hind wings is put forward. This can assist the design of new deployable micro air vehicles and bioinspired deployable systems.
Keywords: bioinspiration; diving beetles; hydraulic mechanism; wings; micro air vehicles (MAVs)